2021
DOI: 10.3390/pathogens10060670
|View full text |Cite
|
Sign up to set email alerts
|

The M35 Metalloprotease Effector FocM35_1 Is Required for Full Virulence of Fusarium oxysporum f. sp. cubense Tropical Race 4

Abstract: Fusarium oxysporum f. sp. cubense tropical race 4 (Foc TR4) causes Fusarium wilt of banana, the most devastating disease on a banana plant. The genome of Foc TR4 encodes many candidate effector proteins. However, little is known about the functions of these effector proteins on their contributions to disease development and Foc TR4 virulence. Here, we discovered a secreted metalloprotease, FocM35_1, which is an essential virulence effector of Foc TR4. FocM35_1 was highly upregulated during the early stages of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…are characterized by displaying a catalytic metal in the active site of the protein and a conserved consensus HEXXH motif. Lastly, the function of metalloprotease, belonging to the family M35, has been widely investigated in fungal genomes, and has been associated with facilitating the penetration of Sordariomycetes species in insect cuticles [76] or in plant hosts [77]. We also compared the profile of fungal-specific transcriptional factors among the Cordycipitaceae species (Figure 6).…”
Section: Genomic Features Of the P Torokii Fjii-l10-sw-p1 Strainmentioning
confidence: 99%
See 1 more Smart Citation
“…are characterized by displaying a catalytic metal in the active site of the protein and a conserved consensus HEXXH motif. Lastly, the function of metalloprotease, belonging to the family M35, has been widely investigated in fungal genomes, and has been associated with facilitating the penetration of Sordariomycetes species in insect cuticles [76] or in plant hosts [77]. We also compared the profile of fungal-specific transcriptional factors among the Cordycipitaceae species (Figure 6).…”
Section: Genomic Features Of the P Torokii Fjii-l10-sw-p1 Strainmentioning
confidence: 99%
“…Proteases are capable of breaking down protein substrates using a universal mechanism of activation of water by Zn 2+ ions and display multiple physiological functions [93]. Different families of metallopeptidases produced by pathogenic fungi are related to critical biological processes as well pathogenesis to human, plants, and insects [77]. More specifically, enzymes of the M24B family cleavage the N-terminal amino acid from peptides harboring a proline residue at the second position and are essential for cellular metabolic processes [94].…”
Section: Metabolomic Profiling Of P Torokii Fjii-l10-sw-p1 Strainmentioning
confidence: 99%
“…Similarly, the secreted cerato‐platanin protein FoCP1 is also required for the virulence of F. oxysporum on host plants (Liu et al, 2019 ). The M35 metalloprotease effector, another secreted protein, is also essential for full virulence (Zhang et al, 2021 ). In addition, FoEG1 can modulate host immunity and is required for the virulence of F. oxysporum (Zhang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Foc4 has been further divided into tropical race 4 (Foc TR4) and subtropical race 4 (Foc STR4), which affect the Cavendish bananas in the tropics and subtropics, respectively ( Ploetz, 2015 ). Among Foc races, Foc TR4 has the strongest pathogenicity, and spread from the Asia-Pacific region to the Middle East, Africa, Australia, and Latin America ( Thangavelu et al, 2021 ; Zhang et al, 2021 ). Despite the serious damage caused by Foc TR4, efficient strategies for its management are not available to date and the understanding of its pathogenesis is still rudimentary ( Liu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Foc-banana interactions, effectors have been proven to act as pathogenicity factors and play important roles during the early infection stages ( Czislowski et al, 2018 ). Previous studies have reported several effectors in Fusarium oxysporum , including secreted in xylem (SIX; Czislowski et al, 2018 ), Necrosis proteins (NPP1; Oome et al, 2014 ), Cerato-Platanin ( Liu et al, 2019 ), hydrophobins ( Casarrubia et al, 2018 ), and M35 family metalloproteinases ( Zhang et al, 2021 ), which are all required by Foc4 for its penetration and full virulence.…”
Section: Introductionmentioning
confidence: 99%